(untitled) (International conference on multidisciplinary science, 2024)
This paper explores the impact of globalization, digitization, and Islamic fintech on the evolving landscape of global finance, with a focus on Islamic banking. It discusses the growth of Islamic banking driven by the Muslim population’s rise, the role of state intervention, and the promising future of Islamic financial technologies. The challenges, including regulatory issues and the need for skilled personnel, are addressed. The paper emphasizes the potential of Islamic fintech to attract millions of new customers and its significance in providing transparent and ethical financial solutions. The study concludes by highlighting the importance of preparedness, regulatory compliance, and collaboration between traditional and fintech institutions for sustainable development in the Islamic financial sector.